PENGARUH KOMUNIKASI, MOTIVASI DAN KOMPETENSI TERHADAP KEPUASAN KERJA PADA PT SINAR UNGGUL PRATAMA - Elvy; Purba, Daris (LPPM Universitas Putera Batam, 2022)
Personal or human resources in a company is one of the supporting variables in achieving goals. The most essential thing a firm can do to its help to grow the potential of its employees is to first measure employee satisfaction. Productivity, quality and service will all increase if employees enjoy their work. In this research, the independent variables are communication, motivation, and competence that affect job satisfaction. Researchers took quantitative methods in its preparation. Researchers based their findings on data gathered from PT Sinar Unggul personnel, there were 112 questionnaires distributed to respondents to answer which will be collected using the SPSS version 25 software.The results of tests conducted through SPSS version 25 prove that communication does not have a significant effect on job satisfaction. The results of multiple regression tests have a value of 0.291. The T_count value is 2.083 >T_(table )1.982 and the significance value is 0.04< from 0.05. Motivation has no significant effect on job satisfaction. Multiple regression test results have a value of -0.262. T_count value -1.019 <T_(table )1.982 and significance value 0.311 > of 0.05. It can be concluded that H2, which is motivation partially has no effect on job satisfaction. Competence has a significant effect on job satisfaction. Multiple regression test results have a value of 0.142. The T_count value is 0.464 <T_(table )1.982 and the significance value is 0.644 > from 0.05. Communication, motivation and competence simultaneously have a significant influence on purchasing decisions. The value of f_count is 1.915 <f_(table )3.08 and the significance value is 0.132 > of 0.05. It can be concluded that H1 which is communication partially has an effect on job satisfaction, H2 partially has no effect on motivation, H3 partially has no effect on job satisfaction.